2021
DOI: 10.1186/s13052-021-01150-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of recurrent respiratory infections

Abstract: Recurrent respiratory infections (RRIs) are a common clinical condition in children, in fact about 25% of children under 1 year and 6% of children during the first 6 years of life have RRIs. In most cases, infections occur with mild clinical manifestations and the frequency of episodes tends to decrease over time with a complete resolution by 12 years of age. However, RRIs significantly reduce child and family quality of life and lead to significant medical and social costs.Despite the importance of this condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 101 publications
(129 reference statements)
0
34
0
10
Order By: Relevance
“…In particular, consistent with other studies, we confirmed that most patients suffered from recurrent respiratory infections [ 36 ]. It should be noted that in the normal population 6–7.4% of children during the first 6–10 years of life have recurrent respiratory infections, including otitis and upper and lower airway infections [ 37 , 38 ]. In our cohort of AT patients, we found a slight higher incidence of common infections of childhood, including otitis or sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, consistent with other studies, we confirmed that most patients suffered from recurrent respiratory infections [ 36 ]. It should be noted that in the normal population 6–7.4% of children during the first 6–10 years of life have recurrent respiratory infections, including otitis and upper and lower airway infections [ 37 , 38 ]. In our cohort of AT patients, we found a slight higher incidence of common infections of childhood, including otitis or sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Physical phenotypes, including auxologic features, behavioral or psychiatric disorders, immunological profile, and genomic analysis were evaluated. Frequent morbidity was reported using recurrent respiratory infections (RRIs), according to the previously described RRI criteria [ 12 ]. The analysis of 25-hydroxyvitamin D (25OHD) levels was limited to patients who did not initially receive vitamin D supplementation; 25OHD levels were considered deficient for values < 20 ng/mL, according to the Institute of Medicine (IOM), the American Academy of Pediatrics (AAP), and the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) recommendations [ 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, future large and methodologically adequate studies in predisposed children are needed to clearly identify the lowest serum vitamin D level associated with a significant increased risk of respiratory infections, in adjunct with the most effective dosage, regimen and duration of vitamin D supplementation [ 158 ]. Similarly, an Italian inter-society consensus on the prevention of recurrent respiratory infections found that reduced vitamin D levels are associated with an increased incidence of viral respiratory infections in the first years of life [ 159 ]. Even if the evidence was too low to universally recommend vitamin D supplementation only for the prevention of respiratory infections, populations with low socioeconomic status and severe vitamin D deficiency, and children with recurrent acute otitis may benefit from vitamin D supplementation for such purpose.…”
Section: Vitamin D Supplementation In Childhoodmentioning
confidence: 99%